A case study exploring disability inclusion within the Muslim Ummah in South Africa - Mayat, Nafisa Essop (Division of Disability Studies, 2023)
Religion and spirituality are central to the way many people, including persons with disabilities, make sense of both the world itself, and their place in that world. However, in most scholarship focusing on disability, religion, as a way of understanding and dealing with disability, is side-lined or absent (Imhoff, 2017). Islam has a long rich history in South Africa and is currently one of the major religions here (Mahida, 2012). Followers of Islam are commonly referred to as members of the Muslim Ummah as a collective, an Ummah that includes persons with disabilities and non-disabled persons. Given the paucity of research focusing on disability in the Muslim Ummah in South Africa, this study sets out to gain insight into the way disability inclusion is enacted within the Muslim Ummah in South Africa. The research question asks: How is disability inclusion interpreted, experienced and enacted by people within the Muslim Ummah in South Africa? Adopting an interpretative qualitative research approach and applying an intrinsic case study method, the research was conducted with members of the Ummah in three major cities in South Africa, viz. Durban, Johannesburg and Cape Town. Data was generated from persons with disabilities, family members of persons with disabilities, the Ulema and a non-disabled person from the Ummah from each city. In-depth face-to-face interviews and a review of three Muslim publications were used as data gathering mechanisms. Interviews were held with seven persons with disabilities, either a physical or sensory disability, five family members of participants with disabilities, six Ulema and three non-disabled persons. All participants were aged 18 and older. Data was analysed by looking for themes that emerged from the data. Three themes, “Seen as Inferior'', “Carrying the Weight for Inclusion” and “We Are Not Doing Enough”, each with two sub-themes, emerged from the analysis. “Seen as Inferior'' and its two sub- themes, ‘' Gaze of Othering and ‘'The Deep Impact of Disability'', highlight the way in which persons with disabilities are viewed as inferior within the Ummah and how this is reflected in the gaze of non-disabled persons on persons with disabilities and their families, and the impact of this gaze. ‘'Carrying the Weight For Inclusion” emphasises the responsibility that persons with disabilities have assumed in order to be accepted into and included in the Ummah and this is demonstrated through the two sub-themes, “The Unspoken Responsibility of Negotiating Persons with Disabilities” and ‘'Negotiating the Effort to be at the Masjid”. “We Are Not Doing Enough” explains that although some aspects of inclusion are evident within the Muslim Ummah, the pace of change is very slow and inclusion remains inadequate. Sub-themes ‘'Inclusion could Create Ease and Belonging” and “Still a Journey to Travel to be Included” capture the way disability inclusion is interpreted and experienced by the participants of the study, highlighting that much work is still needed to attain full inclusion and to create ease and belonging for persons with disabilities within the Ummah. The discussion explains how the dominant discourse around disability is one that reflects an ableist, normative, colonial narrative. This narrative influences how disability inclusion is enacted within the Ummah, belabouring a move to full inclusion. The phenomenon of an unconscious exclusion of persons with disabilities within the Ummah is discussed as it emerges from this dominant discourse, together with the silence that sustains the continuation of the exclusion. The ways in which this unconscious exclusion plays out in many spaces and places significant to the lives of persons with disabilities are identified. It is proposed that, in order to achieve full inclusion and belonging for persons with disabilities within the Ummah, there needs to be a re-shaping in the thinking around disability through generating new knowledge and by challenging the dominance of the normative, ableist narrative. Informed by a decolonial turn, pathways towards full inclusion and belonging of persons with disabilities within the Ummah are proposed. It is suggested that collective action by both persons with disabilities and non-disabled persons within the Ummah is needed for full inclusion and belonging to transpire. The pathway to full inclusion and belonging would enable systemic change around disability within the Ummah to ensue and it would help move the de-colonisation project forward.